Exploring COVID-19 prevention and control design strategies used in the interiors of selected dental clinics - Pabustan, Jezi Nadine A. (College of Home Economics, University of the Philippines Diliman, 2023)
In 2020, the government and other health organizations such as the Philippine Dental Association (PDA) released a series of health guidelines and protocols to prepare for the resumption of dental services and clinics. These guidelines are only highly recommended and it is up to the oral healthcare professionals themselves to decide which of these they are going to implement in their clinics. These situations may pose potential health and safety risks to the patients and staff in dental clinics, increasing the possibility of transmission of COVID-19 and other highly infectious diseases. This exploratory qualitative study examined the different prevention and control design strategies that oral healthcare professionals implemented in their dental clinics, as well as their perceptions of the importance of the interior environment in controlling the spread of infectious diseases. Purposive sampling was used to select ten (10) participants for face-to-face or virtual individual semi-structured interviews with the researcher. Photographs of the participants’ dental clinics were also analyzed and used in the study. Results revealed that the participants prioritized having good ventilation and air quality in their clinics. This is reflected in the types of equipment they purchased and other design strategies they implemented. Their decisions are also influenced by the following: financial costs, spatial and/or structural limitations, comfort and satisfaction, practicality, efficiency, and perceptions of effectiveness, supply, and other personal factors. Lastly, findings showed that the participants generally perceive the interior environment to be important in controlling the spread of infectious diseases, and it is essential to consider its elements in designing and planning for dental clinics in the New Normal and future.